2013
DOI: 10.2478/s11532-013-0338-9
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of reactive dye from aqueous media using Saccharomyces cerevisiae biomass. Equilibrium and kinetic study

Abstract: The biosorption Brilliant Red HE-3B reactive dye by nonliving biomass, Saccharomyces cerevisiae, in batch procedure was investigated. Equilibrium experimental data were analyzed using Freundlich, Langmuir and Dubinin — Radushkevich isotherm models and obtained capacity about 104.167 mg g−1 at 20°C. The batch biosorption process followed the pseudo-second order kinetic model. The multi-linearity of the Weber-Morris plot suggests the presence of two main steps influencing the biosorption process: the intrapartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…It can therefore be said that AB 161 dye has high affinity for S. cerevisiae (Meyen) biomass. Suteu et al (2013) conducted studies on intraparticle diffusion with dead S. cerevisiae biomass and concluded that diffusion is not the driving force of the biosorption process. This likely occurred due to the low affinity between the dye tested and the cell wall of the yeast.…”
Section: Biosorption Kinetic Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…It can therefore be said that AB 161 dye has high affinity for S. cerevisiae (Meyen) biomass. Suteu et al (2013) conducted studies on intraparticle diffusion with dead S. cerevisiae biomass and concluded that diffusion is not the driving force of the biosorption process. This likely occurred due to the low affinity between the dye tested and the cell wall of the yeast.…”
Section: Biosorption Kinetic Studiesmentioning
confidence: 99%
“…The cell wall of S. cerevisiae is composed of chitin, mannoproteins, and glucans (Lipke and Ovalle 1998). Biosorption occurs at low intensities at heterogeneous sites and is predominantly stronger at a specific site (Suteu et al 2013).…”
Section: Isotherm Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Suteu vd. çalışmalarında Brilliant Red HE-3B rekatif boyasının sulu çözeltilerden giderimini ölü formdaki Saccharomyces cerevisiae ile kesikli sistemde incelemişlerdir [9]. Mahmoud çalışmasında Remazol mavi giderimini Saccharomyces cerevisiae ile tekrarlı-kesikli sistemde incelemiştir [10].…”
Section: Gi̇ri̇ş (Introduction)unclassified